Determination of morphological features and elemental profiles on bullet holes for forensic firearm investigation - Bominathan, Uma Rashmika (2024)
A comprehensive scene reconstruction of firearm-related case requires forensic investigators to examine the bullet holes left on various surfaces to confirm if it was produced by a projectile and to subsequently determine if it was made by a specific ammunition. Evolvement of the design and technology of ammunition could have also led to the variation in bullet hole, particularly from non-conventional ammunition. This study was aimed to characterise bullet impact holes caused by various .38 and 9 mm calibre ammunition through physical and chemical means. Morphological features on the six commonly encountered surfaces such as Perspex, Plywood, Formica Board, metal sheet (cabinet), gypsum dan metal sheet (car door) within a firing scene due to the impacts of projectiles were examined. Later, sample recovered from the inner circumferences of bullet holes were examined by inductively coupled plasma-mass spectrometry (ICP-MS) and atomic absorption spectrometry (AAS) to determine the elemental profiles and compared among the bullet holes caused by the eight different ammunition types, namely Winchester .38 SPL, CBC .38 SPL, SME .38 SPL, SME 9 mm, GECO 9 mm, Advance Rotation Extreme (ARX) 9 mm, Ruag Ammotech 9 mm, and Sellier & Bellot 9 × 19. Through physical examination, perfect circular holes were observed with orthogonal angle impact, except for bullet holes impacted by the projectiles from ARX and GECO with the production of flower-like petalling effect at the edge of crater. On the other hand, full metal jacket (FMJ) and jacketed deform projectile (JDP) tends to transfer their materials onto the inner circumference of bullet holes, forming metallic rings. Stubbing procedure was found effective in recovering trace residues from bullet holes. Through ICP-MS detection, lead was found to be the major composition in six types of projectiles, except in ARX and GECO where copper dominated the elemental composition. Antimony, arsenic, bismuth, iron, silver, tin, and zinc were detected as minor composition. However, from the samples recovered from bullet holes, only four elements, namely antimony, copper, lead, and zinc, were successfully detected. Decomposition by principal component analysis (PCA) formed six clusters in the score plots in which impact marks of similar elemental profiles tend to cluster closely. The developed PCA score-linear discriminant analysis (LDA) model had also achieved an overall correct classification up to 85.4% in predicting the projectiles that impact a surface. To conclude, a thorough physical examination and chemical analysis aided in distinguishing the bullet impact holes made by different ammunition. Such important information possesses great potential in forensic investigation, especially in shooting cases.